The Implementation of PV-Battery Storage-Wind Turbine-Load- on Grid System - Muftah Ali (Brilliance: Research of Artificial Intelligence, 2023)
The system is designed to promote the use of renewable energy sources and reduce dependence on non-renewable energy sources such as fossil fuels. The system comprises several components, including photovoltaic (PV) panels, wind turbines, battery storage, load management, and the main grid. The integration of these components provides a reliable and stable source of electricity for households and businesses, particularly in areas prone to power outages. The battery storage system helps to balance the intermittent nature of renewable energy sources, providing a more consistent supply of electricity. Additionally, this system can reduce the carbon footprint of the electricity generation process and contribute to mitigating the effects of climate change. Overall, the implementation of a PV-battery storage-wind turbine-load-main grid system has the potential to transform the way we generate and consume electricity, creating a more sustainable and resilient energy system for future generations.